2006
DOI: 10.1287/mnsc.1060.0658
|View full text |Cite
|
Sign up to set email alerts
|

Location Choices Across the Value Chain: How Activity and Capability Influence Collocation

Abstract: There has been a recent revival of interest in the geographic component of firm strategy. Recent research suggests that two opposing forces--competition costs and agglomeration benefits--determine whether firms collocate in a given geographic market. Unexplored is (1) whether these forces have different impacts on R& D, production, and sales subsidiaries, leading to diverse collocation levels, and (2) how firm capabilities impact collocation by increasing or decreasing competition costs and agglomeration benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(175 citation statements)
references
References 26 publications
9
161
0
2
Order By: Relevance
“…These new establishments often belong to firms that participate in like clusters in other locations, suggesting that firms may seek complementary regional clusters, benefiting from the comparative advantages of each location. While more research is needed, regional clusters may integrate into national and global value chains often through complex networks of subsidiaries of multi-location firms (Dunning 1998;Porter 1998b;Enright, 2000;Alcacer, 2006). Drawing on international business studies, future work should further study the attributes of clusters that are more attractive for multi-location firms, and how their participation in multiple clusters affect the organization and performance of these firms, and how they contribute to entrepreneurship in a particular regional cluster.…”
Section: Conclusion and Extensionsmentioning
confidence: 99%
“…These new establishments often belong to firms that participate in like clusters in other locations, suggesting that firms may seek complementary regional clusters, benefiting from the comparative advantages of each location. While more research is needed, regional clusters may integrate into national and global value chains often through complex networks of subsidiaries of multi-location firms (Dunning 1998;Porter 1998b;Enright, 2000;Alcacer, 2006). Drawing on international business studies, future work should further study the attributes of clusters that are more attractive for multi-location firms, and how their participation in multiple clusters affect the organization and performance of these firms, and how they contribute to entrepreneurship in a particular regional cluster.…”
Section: Conclusion and Extensionsmentioning
confidence: 99%
“…Starting with seminal work by Marshall (1920), researches have shown that firms in an industry cluster benefit from knowledge outflows to competitors, access to specialized labor, and access to specialized intermediate inputs. Among the various activities along the value chain, R&D activities benefit the most from knowledge transfer between competitors, and thus show the highest level of concentration (Audretsch and Feldman 1996;Alcácer 2006). Geographic proximity enables frequent interpersonal interactions through existing social networks (Almeida and Kogut 1999) and local -4 -institutions (Gilson 1999;Stuart and Sorenson 2003), which facilitate the transfer of tacit knowledge in technology clusters.…”
Section: Technology Clusters and Multi-location Firmsmentioning
confidence: 99%
“…Alcácer andChung, 2007, Head et al, 1995), the conditional logit model (McFadden, 1974) has been widely used to analyze the location determinants of foreign direct investments. A drawback of this model is the restrictive assumption of independence of irrelevant alternatives (IIA).…”
Section: Methodsmentioning
confidence: 99%
“…Marshall (1920) highlighted three positive externalities that favour geographic concentration of industries: (1) industry demand that creates a pool of specialized labour, (2) industry demand that creates a pool of specialized inputs, and (3) knowledge spillovers among firms in an industry. Of all activities in the value chain, R&D activities benefit the most from knowledge spillovers among competing firms and consequently show the highest level of concentration (Audretsch and Feldman, 1996, McCann and Mudambi, 2004, Alcácer, 2006.…”
Section: Agglomeration Economiesmentioning
confidence: 99%